Comparision of the Effectiveness of Fire-proof Impregnation Methods for Scots Pine Wood Used in Buildings Construction - Janiec, Mateusz Michał; Szczerba, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The fight for a healthy and clean climate forces many restrictive changes to European law. Wooden construction fits very well into these changes, as it is able to store carbon dioxide for years. Unfortunately, many regulations, e.g. fire regulations, still hinder the development of this type of structures in Poland. Wooden elements used that have class D must achieve class B of fire resistance. For this purpose, they are modified with flame retardant agents. Three salt flame retardants based on: 1-phosphorus and iron, 2-phosphorus and nitrogen and 3-ogranic componds including benzoates, were used in the tests.
Keywords: effectiveness of reaction to fire; fire retardant treated wood; surface impregnation; vacuum impregnation; impregnation rate